2019
DOI: 10.1002/ece3.5329
|View full text |Cite
|
Sign up to set email alerts
|

Multiple aspects of the selfing syndrome of the morning glory Ipomoea lacunosa evolved in response to selection: A Qst‐Fst comparison

Abstract: The frequent transition from outcrossing to selfing in flowering plants is often accompanied by changes in multiple aspects of floral morphology, termed the “selfing syndrome.” While the repeated evolution of these changes suggests a role for natural selection, genetic drift may also be responsible. To determine whether selection or drift shaped different aspects of the pollination syndrome and mating system in the highly selfing morning glory Ipomoea lacunosa , we performed multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 90 publications
(170 reference statements)
8
30
0
Order By: Relevance
“…The relative involvement of selection and drift in the evolution of ancillary traits contributing to the selfing syndrome has seldom been examined (but see [5][6][7]). One of the objectives of this study was to determine whether selection has contributed to the evolution of loss of pigmentation in a highly selfing species of morning glory, Ipomoea lacunosa.…”
Section: Introductionmentioning
confidence: 99%
“…The relative involvement of selection and drift in the evolution of ancillary traits contributing to the selfing syndrome has seldom been examined (but see [5][6][7]). One of the objectives of this study was to determine whether selection has contributed to the evolution of loss of pigmentation in a highly selfing species of morning glory, Ipomoea lacunosa.…”
Section: Introductionmentioning
confidence: 99%
“…A second issue that we address is whether reduced nectar production in the selfing I. lacunosa was caused by selection acting directly or indirectly through correlated traits. Rifkin et al (2019b) demonstrated that selection was responsible for reduced nectar production in this species but could not differentiate between direct or indirect selection on this trait. A finding that nectar traits constitute a distinct evolutionary module would imply that much of that selection acted directly on nectar traits.…”
Section: Introductionmentioning
confidence: 83%
“…The repeated evolution of the selfing syndrome (Barrett, 2002;Arunkumar et al, 2015) has fostered studies of its evolution in a wide range of flowering species, including Capsella (Slotte et al, 2012;Sas et al, 2016;Fujikura et al, 2017;Wozniak et al, 2020), Collinsia (Baldwin et al, 2011;Strandh et al, 2017;Frazee et al, 2021), Mimulus (Fenster & Ritland, 1994;Fishman et al, 2002Fishman et al, , 2015, and Ipomoea (Duncan & Rausher, 2013b;Rifkin et al, 2019bRifkin et al, , 2021. Although several studies have identified quantitative trait loci (QTLs) to assess the degree to which the evolution of different syndrome traits have evolved in a correlated fashion, most have focused on herkogamy, floral size, time to flowering, and pollen size and number (Rifkin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…1D; Table S1) under common greenhouse conditions (see Rifkin et al. 2019b for details; these are a subset of the plants used for Q ST estimation in that study). Briefly, seeds were scarified and germinated in soil in a growth room under a long‐day cycle (16:8 light:dark) and shifted to a short‐day cycle (12:12 light:dark) after approximately four weeks.…”
Section: Methodsmentioning
confidence: 99%